ANALISIS KINERJA KEUANGAN PADA PT. JAYA GEMILANG MANDIRI DI SAMARINDA - Dana Solihin, Sumiatun Robin Jonathan (EKONOMIA, 2018)
The purpose of this study was to find out and analyze the decline in financial performance at PT. Jaya Gemilang Mandiri in Samarinda in 2015 - 2016 measured by Current Ratio and Cash Ratio, Total Debt to Total Asset Ratio and Debt to Equity, Return On Assets and Net Profit Margin, Working Capital Turnover and Fixed Assets Turnover. The analytical tool used is the Current Ratio and Cash Ratio for liquidity ratios, Total Debt to Total Asset Ratio and Debt to Equity for solvency ratios, Return On Assets and Net Profit Margins for profitability ratios and Working Capital Turnover and Fixed Assets Turnover for activity ratios. The research data needed is 2015 - 2016. The results showed. the Current Ratio has decreased by 0.20% and the Cash Ratio by 4.80%, the Total Debt to Total Asset ratio has decreased by 1.67% and Debt to Equity by 2.61%, Return On Assets decreased by 2.77% and Net Profit Margin by 7.35%, Working Capital Turnover decreased by 54.96 times and Fixed Assets Turnover by 4.59 times.Â